Care Received by Women during Labour at a Tertiary Level Hospital, Nepal - Beduka; Rai, Gayatri; Pokhrel, Nirmala; Shrestha, Mangala; Chaudhari, Kriti (Journal of Nursing Education of Nepal, 2023)
Introduction: The adequacies of health care services women receive during pregnancy; intra-natal and  postnatal periods are crucial for the survival and well-being of the mother and her new-born. The aim  of study was to assess care received by women during labour. Care during labour is directed towards  achieving the best possible physical, emotional, and psychological outcome for the woman. Methods: A descriptive observational design was used in the study. Hundred and fifteen women in  active labour were selected through non-probability purposive sampling method. Data were collected  by using structured observational checklist and entered in SPSS version 16. Data were analysed by  using descriptive statistics i.e. frequency, percentage, mean and standard deviation. Results: Women received adequate care (81.2%) in Infection Prevention (IP), communication, support,  and companionship (70.1%), respectful maternity care (79.7%), first stage of labour (62.4%), second  stage of labour (56.9%), third stage of labour (98.8%) and recording and reporting (78.2%). But in  overall, only few (3.5%) women received adequate care and almost all(96.5%) of women received  average care with mean percentage care score 65.32 ±4.648SD. Conclusion: The study concludes that the highest proportion of women received average care during  labour and only few women received adequate care. Minimal or poor care practices were observed in  the use of personal protective device and newborn care. The study suggests that equal focus should be  given in all domains of maternity care with due respect while caring to the woman during labour.
Keywords: Care; Labour; Quality; Women